2014
DOI: 10.1016/j.tem.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Protein and amino acid restriction, aging and disease: from yeast to humans

Abstract: Many of the effects of dietary restriction (DR) on longevity and health span in model organisms have been linked to reduced protein and amino acid (AA) intake and the stimulation of specific nutrient signaling pathways. Studies in yeast have shown that addition of serine, threonine, and valine in media promotes cellular sensitization and aging by activating different but connected pathways. Protein or essential AA restriction extends both lifespan and healthspan in rodent models. In humans, protein restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
167
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(170 citation statements)
references
References 81 publications
(135 reference statements)
2
167
0
1
Order By: Relevance
“…Meanwhile, feed intake was significant higher in the lysine-restricted group than that in the control group, which is contrast with the effect of protein restriction on feed intake [1]. These results concluded that lysine limitation failed to contribute to the merit of protein restriction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, feed intake was significant higher in the lysine-restricted group than that in the control group, which is contrast with the effect of protein restriction on feed intake [1]. These results concluded that lysine limitation failed to contribute to the merit of protein restriction.…”
Section: Discussionmentioning
confidence: 98%
“…Dietary restriction is a promising therapeutic potential for preventing aging-related diseases and extending healthspan via mediating feeding behavior and metabolic reprograming, especially for protein restriction [1-4]. Lysine serves as a key building block for protein synthesis and has been classified as an essential amino acid in humans and animals [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, glucose metabolism alone does not supply all the required building blocks necessary for cell-proliferation and cancer cells therefore depend on the availability of amino acids, particularly glutamine, as a nitrogen source (Vander Heiden et al, 2009). In line with this requirement of cancer cells, protein/amino acid restriction have been demonstrated to delay the onset of many aging-related diseases, including cancer, and increase longevity (Mirzaei et al, 2014). …”
Section: Fasting In Cancer Treatmentmentioning
confidence: 99%
“…The favorable impact of mid-life protein restriction might be anticipated, given that diets restricted in proteins or essential amino acids, consumed in unrestricted amounts, have been shown to boost mean and maximal lifespans in rodents (Mirzaei et al 2014;Sanchez-Roman and Barja 2013). A recent study evaluating the impact of ad libitum diets of widely varying macronutrient composition on longevity in mice found that the highest mean and maximal lifespan was seen in mice consuming a diet providing 5 % protein and 75 % carbohydrates (Solon-Biet et al 2014).…”
mentioning
confidence: 99%